Biophysical features of cereal endosperm that decrease starch digestibility. (1st June 2017) - Roman, Laura; Gomez, Manuel; Li, Cheng; Hamaker, Bruce R.; Martinez, Mario M.
Graphical abstract: Highlights: The effect of endosperm hardness on the digestibility of maize flours was studied. Hard endosperm resulted in flours with more peripheral damage within starch granules. Flours from hard endosperm were digested faster than soft counterparts before cooking. Flours from hard endosperm were digested slower than soft counterparts after cooking. The hard endosperm plant tissue matrix limited starch gelatinisation during cooking. Abstract: The influence of the physical structure of cereal endosperm on the natural structural integrity (intact cells) and starch bioaccessibility of the resultant flours was studied using maize as example. Endosperm hardness, defined by its intracellular (protein matrix) and extracellular (cell walls) constituents, affected the granular and molecular damage of the starch of the resultant flours leading to higher digestibility of raw hard than soft endosperm flours, but comparatively lower digestibility after cooking. After milling, hard endosperm possessed more damaged starch (radial splitting of amylopectin clusters) in the periphery of the resultant particles that increased in vitro starch digestibility of raw flours. Conversely, the hard endosperm plant tissue matrix significantly limited water availability and heat transfer on starch gelatinisation, thereby decreasing the digestion rate after hydrothermal processing (in particle size flours >80 μm). This study provides a unique mechanistic understanding to obtain cereal flours with slow digestion property for commercial utilisation.